The Effect of Sales Growth, Company Age, Firm Size and Leverage on Tax Avoidance on Trading Service Company and Listed Investments on The Indonesia Stock Exchange in The Period 2017-2021 - Ira Widianingrum; Jaquene Kangra; Siti Dini; Anggono Anggono (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to examine the effect of Sales Growth, Company Age, Firm Size, and Leverage on Tax Avoidance. The research focuses on Trading and Investment Services companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. Data collection took place from the end of November 2022 to the beginning of February 2023, allowing for comprehensive analysis and alignment with relevant literature, such as books and journals. The analysis technique employed is multiple linear regression. The results indicate that, simultaneously, Sales Growth, Company Age, Firm Size, and Leverage have a significant effect on Tax Avoidance. However, when analyzed individually, Sales Growth has no significant effect on Tax Avoidance. Firm Size, Company Age, and Leverage each have a negative and insignificant effect on Tax Avoidance. The Adjusted R Square value is 0.49, indicating that 49 percent of the variance in Tax Avoidance is explained by the independent variables of Sales Growth, Company Age, Firm Size, and Leverage. The remaining 51 percent is influenced by other factors not examined in this study, such as earnings management and dividend policy.